Adaptation of articular chondrocytes to changes in osmolality. - Hopewell, B; Urban, J (2003)
Articular chondrocytes are exposed to a unique osmotic environment, which varies throughout the depth of cartilage, and in response to mechanical loading or pathological conditions. In light of such osmotic variations we investigated the response of chondrocytes cultured in alginate beads to long term hypo- and hyperosmotic challenge. Following pre-incubation at 380 mOsmol, exposure to hyperosmotic conditions (550 mOsmol) initially decreased 35S-sulphate incorporation, but after 24 hours of culture, rates had recovered and surpassed their original levels. MAP kinase inhibitors abrogated this response suggesting their involvement in the adaptation mechanism. Hypo-osmotic challenge caused a decrease in 35S-sulphate incorporation throughout the culture period. These results suggest that osmolality is a powerful regulator of macromolecular synthesis, and that perturbations in the osmotic environment may alter the set point for turnover.